A constituição da escola pública primária no Município de Guaraniaçu: percursos históricos - Zanin , Tatiane (2013)
The essay “The establishment of public schools in Guaraniaçu: historical tours”, has as its study object the public elementary school, in the city named before, between the years 1950-2010. For research, we have established the following objectives: understanding the process of constitution of the public elementary school in Guaraniaçu and highlight the historical elements that contributed to the organization of institutionalized education. In this sense, the research issue was the question: How was the public primary schools in Guaraniaçu in the period between 1950 and 2010? To clarify the research problem, we propose the following questions: What is the socio-historical context of implementation of public schools? What was the first schoolar instituition created in the city? How was the creation process, maintenance and disposal of these institutions in the city? Throughout the development of research, we analyze the appearance of the first educational institutions to the establishment of the public school itself, highlighting the factors that contributed to the expansion process and cessation of the schools of the municipal territory. Accordingly, we discuss about the formation of schoolar groups, with emphasis on the history of Grupo José Francisco School of Rock Pigeon, the first established in the county seat. The research relied on different sources: bibliographic study and research on historical documents, such as minutes meetings, minutes of teachers’ possession, the photographic collection constant in public schools, teachers’ personal collection, interviews with teachers and students, as well as federal state and municipal governments on the subject studied. For theoretical and methodological basis, we rely on the contributions of Saviani (2004, 2005, 2006), Schaff (1991), Bencostta (2005, 2006), Wachowicz (1982, 1988), Birth (2006), Souza (2006, 2009) Vidal (2006), among others. We conclude that the survey, cataloging, analysis and interpretation of primary sources enable the preservation of historical memory location that, in dialogue with the socio-historical context, allows to deepen our knowledge about the history of education.